Beyond Athletic Performance: The Emerging Role of Creatine Supplementation in Clinical Medicine — A Narrative Review - Zimowski, Mateusz; Panas, Zuzanna; Ślinko, Izabela; Kuliś, Gabriela; Dryl-Jarmoc, Ewa; Krawczuk, Kacper; Dziemiańczuk, Jakub; Kadysz, Piotr; Kolanek, Agata; Czajkowski, Mateusz (Quality in Sport, 2026)
Introduction. Creatine monohydrate is among the most extensively researched dietary supplements, yet it remains widely perceived as a tool of athletic performance enhancement. Its fundamental role in cellular energy homeostasis across metabolically demanding tissues — including skeletal muscle, brain, and myocardium — suggests a broader clinical relevance that has not been systematically addressed in recent literature. Materials and Methods. A narrative review was conducted using PubMed and Google Scholar, focusing on peer-reviewed original research, systematic reviews, meta-analyses, and position statements published up to April 2025. Search terms included combinations of "creatine," "creatine monohydrate," "phosphocreatine," and condition-specific terms covering skeletal muscle diseases, neurodegenerative disease, depression, sarcopenia, type 2 diabetes, cancer cachexia, traumatic brain injury, pregnancy, and renal safety. A total of 98 sources were included. Conclusions. Creatine supplementation demonstrates well-established ergogenic efficacy in sport and clinically meaningful benefits in skeletal muscle diseases, sarcopenia, and cognitive ageing. Promising evidence supports its adjunctive role in depression and type 2 diabetes, while data in traumatic brain injury remain largely paediatric. Evidence in cancer cachexia is predominantly negative. The safety profile of creatine monohydrate is reassuring across age groups; the observed rise in serum creatinine represents a pharmacokinetic artefact. Pregnant women and patients with advanced chronic kidney disease require individualised assessment. Across clinical areas, mechanistic evidence is often compelling but large trials with standardised dosing and clinically meaningful endpoints remain scarce. Creatine is not only for athletes — its accessibility, tolerability, and growing clinical evidence base make it a strong candidate for broader integration into clinical practice.